Les relations algéro-françaises depuis 2000 ou la quête d’une improbable refondation - Aomar Baghzouz (L’Année du Maghreb)
Algeria and France cannot but share a common future in light of the multidimensional entanglement of their societies. It is up to the Algerians and the French of good will on both sides of the Mediterranean to work at making their future as mutually supporting and exemplary as possible. If friendship among peoples is not built on treaties but on concrete actions, as French President Sarkozy said, a simplified treaty free of the memory issue could be a first step on the road to Franco-Algerian reconciliation.